Multiphase Flow Dynamics 1 Fundamentals - Kolev, Nikolay Ivanov; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
Multi-phase flows are part of our natural environment such as tornadoes, typhoons, air and water pollution and volcanic activities as well as part of industrial technology such as power plants, combustion engines, propulsion systems, or chemical and biological industry. The industrial use of multi-phase systems requires analytical and numerical strategies for predicting their behavior. In its fourth extended edition the successful monograph package (3z(BMultiphase Flow Dynmics(3y (Bcontains theory, methods and practical experience for describing complex transient multi-phase processes in arbitrary geometrical configurations, providing a systematic presentation of the theory and practice of numerical multi-phase fluid dynamics. In the present first volume the local volume and time averaging is used to derive a complete set of conservation equations for three fluids each of them having multi components as constituents. Large parts of the book are devoted on the design of successful numerical methods for solving the obtained system of partial differential equations. Finally the analysis is repeated for boundary fitted curvilinear coordinate systems designing methods applicable for interconnected multi-blocks. This fourth edition includes various updates, extensions, improvements and corrections.s
From the content: Mass conservation -- Momentums conservation -- Derivatives for the equations of state -- On the variety of notations of the energy conservation for single-phase flow -- First and second laws of the thermodynamics -- Some simple applications of the mass and energy conservation -- Exergy of multi-phase multi-component systems -- One-dimensional three-fluid flows -- Detonation waves caused by chemical reactions or by melt-coolant interactions -- Conservation equations in general curvilinear coordinate systems.
Keywords: Engineering; Thermodynamics; Hydraulic engineering; Engineering; Engineering Fluid Dynamics; Engineering Thermodynamics, Heat and Mass Transfer; Fluid- and Aerodynamics; Thermodynamics